2007
DOI: 10.1016/j.jinorgbio.2007.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Size effect of elemental selenium nanoparticles (Nano-Se) at supranutritional levels on selenium accumulation and glutathione S-transferase activity

Abstract: It has been shown that 36 nm Nano-Se has lower toxicity than selenite or selenomethionine, but these forms of selenium (Se) all possess similar ability to increase selenoenzyme levels. The size of nanoparticles plays an important role in their biological activity: as expected, 5-200 nm Nano-Se can directly scavenge free radicals in vitro in a size-dependent fashion. However, in Se-deficient cells and Se-deficient mice, the size effect of Nano-Se on increasing selenoenzymes and liver Se disappears unexpectedly.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
124
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(130 citation statements)
references
References 39 publications
5
124
0
1
Order By: Relevance
“…A wide variety of properties shown by selenium nanoparticles are free radical scavenging (Huang et al 2003), antioxidant (Forootanfar et al 2014;Kong et al 2014;Mittal et al 2014;Ramya et al 2015;Rezvanfar et al 2013;Torres et al 2012;, chemoprotection against chemotherapy-induced reproductive toxicity (Rezvanfar et al 2013) and UV-induced DNA damage (Prasad et al 2013), immunomodulatory, anti-inflammatory (Wang et al 2014), nanomedicinal , chemotherapeutic and chemoprevention against human melanoma and hepatoma cancers Estevez et al 2014;Peng et al 2007), biofortification (Durán et al 2015), and antitumor and anticancer (Jia et al 2015;Kumar et al 2015;Mittal et al 2014;Ren et al 2013) activities. Other applications include antibacterial, antibiofilm (Bartůněk et al 2015;Hariharan et al 2012;Huang et al 2016;Mittal et al 2014;Ramya et al 2015;Shakibaie et al 2015;Tran and Webster 2011;Wang and Webster 2013), antifungal, antiprotozoan, antitapeworm (Bartůněk et al 2015), antiviral, wound healing (Ramya et al 2015), and cytotoxic (Forootanfar et al 2014;Ramya et al 2015) activities.…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of properties shown by selenium nanoparticles are free radical scavenging (Huang et al 2003), antioxidant (Forootanfar et al 2014;Kong et al 2014;Mittal et al 2014;Ramya et al 2015;Rezvanfar et al 2013;Torres et al 2012;, chemoprotection against chemotherapy-induced reproductive toxicity (Rezvanfar et al 2013) and UV-induced DNA damage (Prasad et al 2013), immunomodulatory, anti-inflammatory (Wang et al 2014), nanomedicinal , chemotherapeutic and chemoprevention against human melanoma and hepatoma cancers Estevez et al 2014;Peng et al 2007), biofortification (Durán et al 2015), and antitumor and anticancer (Jia et al 2015;Kumar et al 2015;Mittal et al 2014;Ren et al 2013) activities. Other applications include antibacterial, antibiofilm (Bartůněk et al 2015;Hariharan et al 2012;Huang et al 2016;Mittal et al 2014;Ramya et al 2015;Shakibaie et al 2015;Tran and Webster 2011;Wang and Webster 2013), antifungal, antiprotozoan, antitapeworm (Bartůněk et al 2015), antiviral, wound healing (Ramya et al 2015), and cytotoxic (Forootanfar et al 2014;Ramya et al 2015) activities.…”
Section: Introductionmentioning
confidence: 99%
“…Selenium (Se) is well known to be essential for growth (Yoon et al 2007;Wang and Xu 2008), feather development (Edens et al 2001;Perić et al 2009), immune competence (Cai et al 2012;Liao et al 2012), antioxidant (Peng et al 2007;Zhou and Wang 2011) and reproduction (Poley et al 1937;Leeson et al 2008) of chickens. Inorganic Se salts, such as sodium selenite, are generally supplemented in diets to meet the Se requirement of chickens (Perić et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…When the FDA first permitted the usage of Se yeast in poultry diets in 2001, Se yeast products have been developed and reported to be more effective than inorganic Se used in chicken feeds (Rayman 2004;Ševčíková et al 2006;Yoon et al 2007). Nano red elemental Se was a new Se source, which has novel characteristics such as a large surface area, high surface activity, high catalytic efficiency, strong adsorbing ability and low toxicity (Zhang et al 2001;Peng et al 2007;Wang et al 2007). Mennini (2012) reported that Nano-Se and selenite could similarly increase tissue Se and glutathione peroxidases in Se-deficient rats, which indicated that the bioavailability of the two Se forms was similar.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous research, 5-200 nm of SeNPs showed high bioactivity and directly scavenged free radicals in vitro [23,24]. …”
Section: Biosynthesis Of Senps With Bacillus Licheniformismentioning
confidence: 88%
“…The concentrations of DON and selenium in the experiment were set based on previous studies [21][22][23], and the experimental diet was designed according to NRC (1994) requirements. The ingredients and chemical composition of the basal diet is shown in Table 1.…”
Section: Hens and Housingmentioning
confidence: 99%